IMPLEMENTASI KEBIJAKAN PENGELOLAAN SAMPAH MELALUI PENGOLAHAN DENGAN SISTEM REDUCE REUSE RECYCLE BERBASIS MASYARAKAT DI KABUPATEN SOLOK - Krisnawansyah, Yahya (Ensiklopedia of Journal, 2021)
This research aims at the waste management program through community-based 3R system in various regions. Solok regency is one of the area that has the problems in the management of garbage, this problem became the issue because of the processing facilities of garbage based on 3R system is not maximized absolutely by the government of Solok regancy. This research uses the theory that said by Van Meter Van Horn which consists of six variables: Standard and Policy Purposes, Resources, Inter-Organization Communication, Implementing Attitudes, Implementing institution Characteristics, Environmentally Social, Economics and Politics. The result of this research shows that The implementation of Garbage Management Policy of TPS 3R based on the community in Solok Regency which has not working well and having many obstacles was seen from 6 variables. The first is the standards and policy goals are not completely well. The Second is the financial support and human resources are insufficient. The Third is the Communication between implementing agencies is not well established. The fourth8 is the characteristics of the implementing agency has not been established well. The fifth is the attitude of executors who are still not professional. The last is social environmentally, economics and politics that has not manage well.Keyword: Implementation of the Reduce Reuse Recycle-based Community Waste Management Policy.